Structures, processes and outcomes of specialist critical care nurse education: An integrative review. Issue 4 (July 2019) - Gullick, Janice; Lin, Frances; Massey, Debbie; Wilson, Lorraine; Greenwood, Melanie; Skylas, Katina; Woodard, Mark; Tembo, Agness C.; Mitchell, Marion; Gill, Fenella J.
Abstract: Objectives: The objective of this study was to review and synthesise international literature to reveal the contemporary structures, processes, and outcomes of critical care nurse (CCN) education. Method: An integrative review on specialist critical care education was guided by Whittemore and Knafl's integrative review steps: problem identification; literature search; and data evaluation, analysis, and presentation. Donabedian's Quality Framework (Structure-Process-Outcome) provided a useful analytical lens and structure for the reporting of findings. Results: (1) Structures for CCN education incorporated transition-to-practice and ongoing education programs typically offered by hospitals and health services and university-level graduate certificate, diploma, and masters programs. Structural expectations included a standard core curriculum, clinically credible academic staff, and courses compliant with a higher education framework. Published workforce standards and policies were important structures for the practice learning environment. (2) Processes included incremental exposure to increasing patient acuity; consistent and appropriately supported and competent hospital-based preceptors/assessors; courses delivered with a flexible, modular approach; curricula that support nontechnical skills and patient- and family-centred care; stakeholder engagement between the education provider and the clinical setting to guide course planning, evaluation and revalidation; and evidence-based measurement of clinical capabilities/competence. (3) Outcomes included articulation of the scope and levels of graduate attributes and professional activities associated with each level. The role of higher degree research programs for knowledge creation and critical care academic leadership was noted. Conclusions: Provision of high-quality critical care education is multifaceted and complex. These findings provide information for healthcare organisations and education providers. This may enable best practice structures and processes for critical care specialist training that meets the needs of industry and safely supports developing CCN expertise. There is an acknowledged tension between the expectations of governing bodies for policies, standards, and position statements to enhance quality and reduce care variance and the availability of high-quality evidence to underpin these across international contexts.